Koje i kakve reforme preduzeti da bi Bosna i Hercegovina ubrzala svoj put integracije u Evropsku uniju / Which and What Kind of Reforms to Undertaketo Accelerate Bosnia and Herzegovina’s EU Integration Path - Fočo, Salih (Pregled: časopis za društvena pitanja / Periodical for social issues, 2014)
Article of Scientific Debate on the Social Processes in Bosnia and Herzegovina on its Path of EU Ascension, 22 April 2014.